2014
DOI: 10.1063/1.4863501
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of carbon microcoils

Abstract: Carbon microcoils (CMCs) have emerged as versatile material artifacts for a variety of applications due to their helical and spiral structures. Embedded in matrix, CMCs have already been demonstrated for their potential tactile/proximity sensor application. In this study, CMCs were prepared using a conventional chemical vapor deposition method, and then were functionalized with octadecylamine. Upon photoexcitation, the functionalized CMCs exhibited photoluminescence in the visible region, which has never been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hikita et al [66] reported an optical property of octadecylamine (ODA) functionalized CMCs. As shown in Figure 24, ODA functionalized CMCs emitted fluorescent light with a peak of ~423 nm using a 350 nm excitation light source.…”
Section: Functionalization Of Coiled Carbon Filamentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hikita et al [66] reported an optical property of octadecylamine (ODA) functionalized CMCs. As shown in Figure 24, ODA functionalized CMCs emitted fluorescent light with a peak of ~423 nm using a 350 nm excitation light source.…”
Section: Functionalization Of Coiled Carbon Filamentsmentioning
confidence: 99%
“…This occurred by passivation on the surface of the CMC turbostratic structure with ODA [66]. [66]. Reprinted with permission from [66], Copyright 2014 AIP Publishing LLC.…”
Section: Functionalization Of Coiled Carbon Filamentsmentioning
confidence: 99%
See 1 more Smart Citation